Film thickness measurements in a running hydrostatic unit using ultrasound - Leonhard, L; Marsch, S; Diesselberg, M; Harper, P; Dwyer-Joyce, R S (Tribologia - Finnish Journal of Tribology, 2017)
The present paper describes the measurement of the oil film thickness in the range of a few micrometers in an operating hydrostatic unit using ultrasound. The investigated tribological system consists of a rotating steel cylinder block and a stationary bi-metal valve plate under static and hydrodynamic lubrication. The film thickness has been recorded in a wide range of operating conditions, pressure between 100 to 300 bar and rotational speed between 500 and 3000 rpm, to support a deeper understanding of the system. Temperature sensors were implemented next to the ultrasound sensors to compensate the ultrasound signal amplitude and phase change due to temperature dependent acoustic impedances. To confirm the results, especially the presence of deliberate zero-film conditions, wear profiles of the running surface were taken. The ultrasound technique also allows the real-time observation of film thickness oscillations with shaft and piston frequency. Steady-state measurements confirm the system behavior observed in transient operation and zero-film conditions with respect to hardware configuration were detected. The findings will be utilized to support current product development activities and to validate and improve simulation models used for film thickness predictions.